2020
DOI: 10.1101/2020.07.14.20150243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo Assessment of Neuroinflammation in 4-Repeat Tauopathies

Abstract: Objective: The aim of this cross−sectional single center study was to investigate 18kDa translocator protein (TSPO)−PET as a biomarker for microglial activation in the 4−repeat tauopathies corticobasal degeneration and progressive supranuclear palsy (PSP). Methods: Specific binding of the TSPO tracer 18F−GE−180 was determined by serial PET during pharmacological depletion of microglia in a 4−repeat tau mouse model. TSPO−PET was performed in 30 patients with corticobasal syndrome (CBS, 68±9 years, 16 female) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 42 publications
6
23
0
Order By: Relevance
“…Next, we assessed whether TSPO imaging of skull would give any hints on underlying brain pathologies in human. To this end, we assessed the TSPO-PET signal in the skull of stroke, relapsing remitting multiple sclerosis (RRMS) ( 43 ) and primary progressive multiple sclerosis (PPMS) patients as well as 4-repeat tauopathy (4RT) patients ( 44 ). Our data demonstrated elevated skull inflammation in each cohort of patients with different patterns ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we assessed whether TSPO imaging of skull would give any hints on underlying brain pathologies in human. To this end, we assessed the TSPO-PET signal in the skull of stroke, relapsing remitting multiple sclerosis (RRMS) ( 43 ) and primary progressive multiple sclerosis (PPMS) patients as well as 4-repeat tauopathy (4RT) patients ( 44 ). Our data demonstrated elevated skull inflammation in each cohort of patients with different patterns ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trial of PET using [ 11 C]ER176 for accessing microglia activation in patients with MCI and AD is still ongoing (NCT03744312). Microglial activation assessed by using [ 18 F]GE-180 in different amyloidosis, tauopathy rodent models have been reported ( 47 , 50 , 53 , 89 , 90 , 92 102 ) ( Table 1 ). López-Picón et al showed that [ 18 F]GE-180 signal reached plateaus at an early stage, while the Aβ load detected by [ 11 C]PIB was still increasing in APP23 mice ( 90 ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…In the case of [ 18 F]PBR111, two independent research groups conducted studies in multiple sclerosis [103,230,231] (Imperial College London, UK) and schizophrenia/psychosis [115,232] (University of Antwerp, Belgium). Among the 6 remaining challengers, 2 were restricted to specific groups of pathologies: [ 11 [81], rheumatoid arthritis [200] and stroke [26]). However, [ 18 F]GE-180 was shown to have slow/poor brain uptake in human [233], and the consequences on quantification and modelling have abundantly debated [234][235][236].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 6 remaining challengers, 2 were restricted to specific groups of pathologies: [ 11 C]DAA1106 and [ 18 F]FEPPA were used only in neurodegenerative diseases and mental disorders ([ 11 C]DAA1106: 20 and 91 patients respectively; [ 18 F]FEPPA: 77 and 337 patients respectively). [ 18 F]GE-180, initially mainly used in patients with multiple sclerosis (45 patients) and brain tumour (68 patients), was recently tested in other pathologies (tauopathies [ 81 ], rheumatoid arthritis [ 200 ] and stroke [ 26 ]). However, [ 18 F]GE-180 was shown to have slow/poor brain uptake in human [ 233 ], and the consequences on quantification and modelling have abundantly debated [ 234 236 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation